Investigation of the Axial Rotor Thrust in Centrifugal Compressors استقصاء الدفع المحورى على العضور الدوار فى الضواغط النابذة - Aly Elzahaby; S. El-Agouz; Ahmed Nemnem; Abdelhady Mubarak (Journal of Engineering Research - Egypt)
الهدف من البحث هو دراسة وتحليل والتعين الدقيق للدفع المحورى علىالعضو الدوار فى الضواغط الطاردة المرکزية. نشرح العوامل التى تؤثر علىالدفع المحورى مثل زيادة الأحمال على ضاغط ثانى أکسيد الکربون عنأوضاع التشغيل التصميمية له . کما تتضمن العوامل تأثير وجود Fouling مع الغاز مما ينتج عنه تراکم على الأسطح الداخلية لدفاعات العضو الدوارفيتسبب فى زيادة الدفع المحورى وتقليل من أداء الضاغط . يتناول البحثشرح العلاقة مابين الدفع المحورى للعضو الدوارفى وجود نسبة Foulingمع الغاز فى خلال فترة زمنية محددة من بعد عمل عمرة کاملة لضاغط ثانىأکسيد الکربون . بعد الدراسة والتحليل نقف على کيفية تقليل الدفع المحورىعلى العضو الدوار وذلک بوضع اسطوانة اتزان على العضور الدوار لخلققوى معاکسة له تتناسب مع جميع الظروف التشغيلية لضاغط ثانى أکسيدالکربون بحيث أن الدفع المحورى للعضو الدوار بعدها لا يتعدى 50 % منحمل الکرسى. النتائج النهائية التى تم الحصول عليها: عند استخدام قطراسطوانة اتزان = 158.6686 mmt D تکون أعلى قيمة للدفع المحورى عنأوضاع التشغيل المختلفة للضاغط هى 93.193 % من حمل الکرسى. عنداستخدام قطر اسطوانة اتزان = 186.065 mmt D تکون أعلى قيمة للدفعالمحورى عن أوضاع التشغيل المختلفة للضاغط هى 73.35 % من حملالکرسى. عند استخدام قطر اسطوانة اتزان = 174.595 mmt D تکونأعلى قيمة للدفع المحورى عن أوضاع التشغيل المختلفة للضاغط هى41.22 % من حمل الکرسى مع وجود Fouling مع الغاز وعند أقصى حملللضاغط بعد العمرة فى عدم وجود Fouling مع الغازهى 0 % من حملالکرسى وهذا يعتبرأنسب قطر يستخدم لاسطوانة الاتزان (Balance drum)لان الدفع المحورى يکون أقل من % 50 من حمل الکرسى.Abstract: This article is a study, analysis, and determine accurately the axial rotor thrust for centrifugal compressors. Are explained the factors that affect axial rotor for carbon dioxide compressor during operating conditions. Also, the effect of the existence of fouling with gas, results in the accumulation of fouling on the internal surfaces of the impellers leading to an increase in axial rotor thrust and reduction of the performance of the compressor. The relationship between axial rotor thrust and fouling ratio with time is discussed after complete overhaul for the carbon dioxide compressor. The axial rotor thrust on the carbon dioxide compressor is reduced by placing balance drum on rotor of the compressor in the opposite direction of the axial force which is suitable for all operating conditions of the compressor. The resultant axial force didn’t exceed 50 % of rated bearing load, and the analysis method is then approved to be effective. The residual thrust load for high pressure rotor for the compressor before modification at design operating condition is equal to 13.68 % of rated bearing load, while at the high load without fouling effect for the compressor is equal to 58.47 % of rated bearing load and compressor with fouling effect is equal to 110.9 % of rated bearing load. When using the balance drum diameter Dt =158.6686 mm, the highest value of axial thrust force is equal to 93.193 % of rated bearing load. When using the balance drum diameter Dt =174.595 mm, the highest value of axial thrust force is equal to 41.22 % of rated bearing load. When using the balance drum diameter Dt =186.065 mm, the highest value of axial thrust force is equal to 73.35 % of rated bearing load.